COMMUNITY BASED CORRECTIONS SEBAGAI ALTERNATIF MODEL PEMBINAAN NARAPIDANA DI MASA MENDATANG - Hamja Hamja (Arena Hukum, 2019)
AbstractCommunity Based Correction is a type of coaching program for Prisoners while serving the rest of their crminal offences, they have been given the opportunity to return to the midst of society with certain supervision. This study aims to determine the extent of the role of the community in fostering prisoners and alternative models of open prisons in the future. This is a descriptive research using qualitative methods and sociological approaches. Data collections includes interviews and observations with prisoner informants and correctional institution officers. The findings of this study indicate that the implementation of guidance involving the community has not fully reflected the application of the principle of Community Based Corrections due to the following inhibiting factors. Firstly, open prisons do not have their own legal umbrella. Secondly, the implementing regulations and fixed procedures for open prisons still use old regulations. Third, open prisons do not have the authority to determine prisoners to be assisted. Fourth, there is no cooperation with third parties. Fifth, the organizational structure does not reflect the actual need for guidance in prisons. Whereas open prisons prioritize the correctional principle itself, so that prisoners can be accepted back by the community.AbstrakCommunity Based Correction adalah jenis program pembinaan bagi Narapidana sewaktu menjalani sisa pidananya, mereka telah diberi kesempatan untuk kembali ketengah-tengah masyarakat dengan pengawasan atau supervisi tertentu. Penelitian ini tujuannya untuk mengetahui sejauhmana peran masyarakat dalam membina Narapidana dan alternatif model Lapas terbuka di masa mendatang. Penelitian ini bersifat deskriptif dengan metode kualitatif dan pendekatan sosiologis. Hasil penelitian ini menunjukkan pelaksanaan pembinaan yang melibatkan masyarakat belum sepenuhnya mencerminkan penerapan prinsip Community Based Corrections karena adanya faktor – faktor penghambat sebagai berikut. Pertama, Lapas terbuka belum mempunyai payung hukum sendiri. Kedua, Peraturan pelaksanaan serta prosedur tetap Lapas terbuka masih memakai peraturan yang lama. Ketiga, Lapas terbuka tidak mempunyai kewenangan untuk menentukan narapidana menjadi warga binaannya. Keempat, Belum ada kerja sama dengan pihak ketiga. Kelima, Struktur organisasi belum mencerminkan kebutuhan pembinaan di lapas yang sebenarnya. Padahal Lapas terbuka mengedepankan prinsip pemasyarakatan itu sendiri yaitu agar narapidana dapat diterima kembali oleh masyarakat.